A Clinicopathologic Evaluation of Incidental Fundic Gland Polyps With Dysplasia: Implications for Clinical Management. (July 2017) - Lloyd, Isaac E; Kohlmann, Wendy K; Gligorich, Keith; Hall, Amy; Lyon, Elaine; Downs‐Kelly, Erinn; Samowitz, Wade S; Bronner, Mary P
Abstract : Objectives: Fundic gland polyps (FGPs) can rarely exhibit dysplasia of the surface epithelium. Based on retrospective data, FGPs with dysplasia (FGPDs) are thought to be a strong marker for familial adenomatous polyposis (FAP), although sporadic, non‐syndromic FGPDs also occur. Owing to the significant syndromic association, diagnosis of an apparently sporadic FGPD may prompt clinical evaluation for FAP, especially its attenuated variant. We sought to evaluate the positive predictive value of incidental FGPDs for FAP. We also characterized the clinicopathologic features of incidental FGPDs to advance clinical management. Methods: Incidental FGPDs were identified from 2004 to 2015 in patients without FAP at biopsy. All clinical follow‐up data were reviewed, and germline analysis for APC and MUTYH mutations was performed in consenting patients. Results: We identified 25 incidental FGPDs in patients not known to have FAP (11.6% of FGPDs, 1.0% of all FGPs). Four patients had a family history of gastric polyps or gastrointestinal cancers. Clinical management included completion polypectomy and gastric endoscopic surveillance (44%), endoscopic surveillance alone (32%), no follow‐up (24%), colonoscopy referral (12%), and genetic counseling (4%). Colonoscopies on record revealed 0–7 cumulative adenomas. Follow‐up averaged 4.4 years (range 0.3–10.6). No clinical evidence of FAP, gastric cancer, death, or surgery occurred. None of the 11 patients consenting to germline APC and MUTYH testing had genomic alterations. Conclusions: Incidental FGPDs in this series were all found to be sporadic (25/25) by endoscopic, clinical, and molecular findings, and thus FGPDs were not harbingers of FAP. As isolated findings, FGPDs do not appear to warrant follow‐up genetic counseling or testing.